Different segmental resection techniques and postoperative complications in patients with colorectal endometriosis: A systematic review. (6th June 2022) - Darici, Ezgi; Salama, Mohamed; Bokor, Attila; Oral, Engin; Dauser, Bernhard; Hudelist, Gernot
Abstract: Introduction: The aim of this study was to analyze the available literature by conducting a systematic review to assess the possible effects of nerve‐sparing segmental resection and conventional bowel resection on postoperative complications for the treatment of colorectal endometriosis. Material and methods: Pubmed, Clinical Trials.gov, Cochrane Library, and Web of Science were comprehensively searched from 1997 to 2021 in order to perform a systematic review. Studies including patients undergoing segmental resection for colorectal endometriosis including adequate follow‐up, data on postoperative complications and postoperative sequelae were enrolled in this review. Selected articles were evaluated and divided in two groups: Nerve‐sparing resection (NSR), and conventional segmental resection not otherwise specified (SRNOS). Within the NSRs, studies mentioning preservation of the rectal artery supply (artery and nerve‐sparing SR – ANSR) and not reporting preservation of the artery supply (NSR not otherwise specified – NSRNOS) were further analyzed. PROSPERO ID: CRD42021250974. Results: A total of 7549 patients from 63 studies were included in the data analysis. Forty‐three of these publications did not mention the preservation or the removal of the hypogastric nerve plexus, or main rectal artery supply and were summarized as SRNOS. The remaining 22 studies were listed under the NSR group. The mean size of the resected deep endometriosis lesions and patients' body mass index were comparable between SRNOS and NSR. A mean of 3.6% (0–16.6) and 2.3% (0–10.5%) of rectovaginal fistula development was reported in patients who underwent SRNOS and NSR, respectively. Anastomotic leakage rates varied from 0% to 8.6% (mean 1.7 ± 2%) in SRNOS compared with 0% to 8% (mean 1.7 ± 2%) in patients undergoing NSR. Urinary retention (4.5% and 4.9%) and long‐term bladder catheterization (4.9% and 5.6%) were frequently reported in SRNOS and NSR. There was insufficient information about pain or the recurrence rates for women undergoing SRNOS and NSR. Conclusions: Current data describe the outcomes of different segmental resection techniques. However, the data are inhomogeneous and not sufficient to reach a conclusion regarding a possible advantage of one technique over the other.